(NmETOD ORIENTACIONNOGO USREDNENIQ W MEHANIKE MATERIALOW (B/s - (NlAGZDINX(B, (NaJWAR vANOWI^s; (NtAMUV(B, (NwITAUT pETROWI^s; (NtETERS(B, (NgUNDARIS aLEKSANDROWI^s; (NkREGERS(B, (NaNDRIS fRICEWI^s ((NrIGA (B:s (NzINATNE(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 184-188 (101 (NNAZW(B.)s
(Nan lATWIJSKOJ ssr(B, (NiN(B-(NT MEHANIKI POLIMEROWs
Keywords: (NfIZI^ESKOE STROENIE MATERIIs